Using Transitional Points in the Optical Injection Locking Behavior of a Semiconductor Laser to Extract Its Dimensionless Operating Parameters - Herrera, Daniel; Kovanis, Vassilios; Lester, Luke (IEEE journal of selected topics in quantum electronics, 2022)
The complete set of intrinsic dimensionless parameters of a packaged and fiber-pigtailed distributed feedback (DFB) semiconductor laser are extracted from the non-linear operational stability boundaries of the optical-injection-locking (OIL) architecture. Specifically, this procedure is done by relating the intrinsic parameters to the injection ratios corresponding to the Hopf bifurcation points at zero detuning, as well as the detuning of the Hopf-Saddle-Node point. The bifurcation points of the injected laser's operational space are found by coupling its output into a high-resolution optical spectrum analyzer. This is enabled by establishing a 30 dB side mode suppression ratio between the central mode and Period 1 oscillations to define the boundaries of Stable Locking. Along with the laser's threshold current and free-running relaxation oscillation frequencies, performing these measurements over a range of pumping values allows for the calculation of the laser's linewidth enhancement factor, irrespective of the device packaging. Utilizing a high pump approximation, the remaining dimensionless parameters are extracted after obtaining the photon lifetime. Using this approach, the operational capabilities of an arbitrarily-packaged laser can be determined, allowing for the analysis of an injected laser's operational space for a variety high-frequency and dynamical applications.